Empreendedoras e criação de negócios : um estudo no setor do vestuário das cidades de Maringá e Cianorte - Fabrício, Joiceli dos Santos (2011)
A significant number of new companies has been created by women entrepreneurs. They are increasingly present in almost all sectors, but gaps remain in the way this group undertakes. In this case, the objective of this study is to describe how occurs the creation of business in the clothing sector of the cities of Maringá and Cianorte. Because of its historical features, this sector has a lot of companies open and management by women. This research is characterized as exploratory of quantitative nature, with data collection through extensive questionnaire. Using closed questions with a group of 102 entrepreneurs sought to identify the profile, characterize the companies and to point how occurred opportunities identification, among other factors. The results indicate that in most cases, the women create their companies between 25 and 35 years old, are married and have children, the main partner is the husband, start with their own money, cares a lot about family support, knows very much about the sector, but don't have training or knows just a little about management experience prior to the creation of the company and nearly half started acting informally. The survey also revealed heavy impact the environment and significant differences in the creation of enterprises depending on the period of creation. The findings highlight the importance of developing public policies that address the specifics of business created by women, as well as the emergence of specific problems still not mentioned in the literature as the lack of role orking formally.